GREEN INNOVATION-ORIENTED STRATEGY AND FINANCIAL PERFORMANCE OF MANUFACTURING MSMES: TOWARD GREEN ECONOMIC SUSTAINABILITY - Hiezkia Xena Saban; Nadya Putri Indraswari; Nurlia; Juwari (KRISNA: Kumpulan Riset Akuntansi, 2026)
The objective of this study is to examine how environmental regulations impact the financial performance of manufacturing MSMEs, taking into account the mediating role of green innovation-oriented (GIO) and the moderating role of green dynamic capability (GDC). A quantitative approach using SEM-PLS analysis was applied to data from 177 respondents in North Balikpapan. The findings indicate that environmental regulations do not directly affect financial performance. However, they significantly enhance GIO, which subsequently has a positive and significant impact on financial performance. Additionally, while GDC directly influences financial performance, it does not moderate the relationship between environmental regulation and financial performance. This study emphasizes the importance of green innovation as a strategic response to regulatory pressures for improving MSME performance in a sustainable manner.